Analisis Pengaruh Kompetensi, Kompensasi DanLingkungan Kerja Terhadap Kinerja Karyawan(Study Kasus Pada Karyawan Waroeng Special Sambal (SS) Di Semarang) - Puspitasari, Dyah; , Ir. Irmawati, SE, Msi (2016)
This research aim to to analyse the interest have an effect on to employees performance Special Waroeng Sambal (SS) Semarang. To analyse the compensation have an effect on to employees performance Special Waroeng Sambal (SS) Semarang. To analyse the environment work to have an effect on to employees performance Special Waroeng Sambal (SS) Semarang. In this research such population all employees at Special Waroeng Sambel (SS) Semarang and sample used in this research 100 employees (responder). Pursuant to result analyse the interest variable have the influence which signifikan to performance employees Waroeng Special Sambal (SS) Semarang. Compensation Variable have the influence which signifikan to performance employees Waroeng Special Sambal (SS) Semarang. Environmental Variable work to have the influence which signifikan to performance employees Waroeng Special Sambal (SS) Semarang. Result of analysis Ftest obtained result Fcount> Ftable (25,580 > 3,15), hence Ho refused, Mean by together interest variable, compensation and environment work by together to performance employees Waroeng Special Sambal (SS) Semarang, so that model in research can be used fit. Result of calculation to assess the R2 obtained in scored a point doubled analysis regresi coefficient determinasi by adjusted-R2 equal to 0,427. Matter this means that 42,7% variation explainable employees performance variable by interest variable, compensation and environment work while the rest that is 57,3% explained by other factors outside accurate model Keyword : Interest, Compensation, Environmental Work and Performance.